PERPUSTAKAAN SEBAGAI RUANG LITERASI CERDAS: PENINGKATAN BUDAYA BACA DAN LITERASI DIGITAL DI DESA EMBUNG KANDONG, KECAMATAN TERARA, KABUPATEN LOMBOK TIMUR - Prawira, Didik; Jurnal Wicara; Septiandari, Olevia; Widiantara, I Nyoman Ari; Amalia, Baiq Jihan; Azzahra, Jasmine Maulida; Sulastri, Emi; Juan, Kemal; Lestari, Neli Aulia; Islaeniah, Irma; Jumhari, Sutrisna; Ayub, Syahrial (Jurnal Wicara, 2025)
The PMD Literacy Community Service Program (KKN) implemented in Embung Kandong Village, Terara District, East Lombok, aimed to revitalize the "Andalan" Village Library, which had been experiencing declining utilization, and to improve community literacy, particularly in reading, writing, and digital literacy. Through a participatory approach, students from the University of Mataram initiated various activities, such as read-alouds, reading coupons, LENTERA, and TANABATA (Literacy Hope Tree), all presented in an interactive and educational manner. Implementation methods included observation, interviews, focus group discussions, and cross-sector collaboration with the village government and local schools. During the 45-day implementation period, activities focused on optimizing the library as a community information and learning center. The program successfully increased community participation in literacy and built collective awareness of the importance of reading as a foundation for developing local potential. Outputs from the program included activity reports, scientific and media publications, product, leaflet, and documentary videos for documentation and dissemination of results. The success of this program demonstrates the importance of synergy between educational institutions and the community in creating a sustainable literacy culture in the village.